The influence of dangerous geological and technogenic processes during engineering and geological research and environmental safety for construction in the modern period - Sokolov, Victor; Sukhov, Valeriy (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Problems Statement and Purpose. Reliability of construction, protection of the territory from dangerous geological and technogenic processes, assessment of impact of construction and reconstruction objects on the environmental safety of the territory should be based on high-quality materials of engineering investigations. Today in Ukraine, the conditions of construction and reconstruction have significantly increased the requirements for the quality and composition of engineering research. At the same time, there are a number of natural and social factors that increase the degree of geotechnical and environmental risks during construction, there is no system that ensures the mandatory implementation of state regulations, which has an extremely negative effect on the quality of research materials. These questions are of particular importance given the volume of work that awaits us in the reconstruction of our country.The purpose of article is to once again draw attention to the problems in the field of engineering and geological investigations for construction, which largely depend on the safety and comfort of our living, to formulate proposals for improving the state of affairs in anticipation of the large-scale recovery of our country and the possibility of entering the regulatory field of the EU.Data & Methods. The legislative framework of Ukraine in the field of engineering and geological investigations for construction has been analyzed.Results. The article provides an analysis of the state with the legislative base in Ukraine regarding engineering surveys, the system that ensures mandatory compliance with the requirements of regulatory documents, factors that increase man-made and environmental risks in construction, proposed measures aimed at improving the quality of survey materials. 4 factors have been established that systematically affect the quality of engineering and geological investigations and the safety of construction: 1) most accidents and deformations of buildings and structures are associated with processes in the "base - foundation" system; 2) about 80% of the territory of Ukraine is characterized by complex engineering and geological conditions, with manifestations of almost all dangerous geological processes: seismicity, karst, landslides, reworking of banks, subsidence, soil swelling, etc.; 3) a significant increase in the specific weight of construction in conditions of dense urban construction and reconstruction of existing buildings in the total volume of construction; 4) social and economic conditions. An example of a change in the qualitative characteristics of underground hydrosphere (chemical composition and increase in the aggressiveness of groundwater), which had an impact on the reliability of construction and the ecological component at the studied area, has been considered.